PERAN KALIGRAFI ISLAM SEBAGAI MEDIA DAKWAH DI ERA DIGITAL - Nabila Arrahma (Jurnal Ekshis, 2025)
Islamic calligraphy, a form of art that beautifully writes Arabic letters and conveys spiritual messages, has played a crucial role in spreading Islamic teachings. With the rise of digital technology, Islamic calligraphy has transformed, offering new opportunities for da’wah (Islamic preaching). This study explores the role of Islamic calligraphy as a medium for da’wah in the digital age, focusing on the impact of modern technology in supporting its development. A qualitative approach with descriptive analysis was used, examining journals, books, and articles. Findings show that digital tools, such as social media platforms and graphic design applications, as well as interactive technologies like augmented reality (AR), have expanded the reach of calligraphy. These innovations allow Islamic calligraphy to engage a broader audience, particularly younger generations, while enhancing its effectiveness as a medium for da’wah. The study concludes that Islamic calligraphy remains a powerful tool for spreading Islamic values in the modern, digital world.